Waist Circumference as a Predictor for Menstrual Cycle Disturbance Among College Student - Bambang Purwanto; Ni Nyoman Trioka Rtamagustini; Hanifa Erlin Dharmayanti (Jurnal Ners, 2018)
Introduction: Menstrual cycle disturbance is the sign of a reproductive health problem, yet the cause tends to be multifactorial. This study aimed to analyze the risk factors of menstrual cycle disturbance which related to nutrition status among college students.Methods: This was an observational analytical study with a cross-sectional approach. There were 59 participants taken as samples according to inclusion criteria using proportionate stratified random sampling. Data were analyzed with chi-square and multiple logistic regression test.Results: Results found that 35.6% of participants experienced menstrual cycle disturbance. Bivariate analysis showed significant correlation between body fat percentage (p= 0.038, OR: 2.417) and waist circumference (p= 0.003, OR: 2.956) with menstrual cycle disturbance, otherwise no correlation found between Body Mass Index (BMI) (p= 0.052, OR: 2.145), subcutaneous fat thickness (p= 1, OR: 1.279), and total cholesterol levels (p= 1, OR: 1.063) with menstrual cycle disturbance. Multiple logistic regression analysis showed that waist circumference became determinant factor among other variables predicting menstrual cycle disturbance in this study (p= 0.002, OR: 7.260).Conclusion: Waist circumference and body fat percentage were both risk factors of menstrual cycle disturbance, yet waist circumference was found being a determinant predictor to predict menstrual cycle disturbance among college student. Female students may pay particular attention to their waist circumference for detection of reproductive health problem earlier, especially regarding menstruation cycle disturbance.